Analysis of the Honorary Payroll Accounting System at the Setdaprovsu Organizational Bureau - Dinda Andriani Marpaung; Hendra Hermain Lubis (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
This study aims to analyze the honorary payroll accounting system at the Regional Secretariat of the Regional Secretariat of the Republic of Indonesia. This study uses a descriptive type of research. The data taken is by using interview techniques. The data analysis technique used is descriptive analysis with a qualitative approach which does not use a formula. The results showed that the honorary payroll accounting system at the Regional Secretariat of the Regional Secretariat was very good and in accordance with existing theories. Based on this discussion, suggestions related to the payroll accounting system at the Regional Secretariat Organization Bureau, namely the payroll accounting system need to be developed again so that future information system developments are needed to adapt to the development of the company or agency.